Interaction between mosquito (Diptera: Culicidae) diversity and phytotelmata used as traps in an Atlantic forest ecosystem, state of Rio de Janeiro, Brazil - Mello, Cecilia Ferreira de; Pavão, Letícia de Mattos; Olsson Freitas Silva, Shayenne; Queiroz, Amanda Bastos; Alencar, Jeronimo (Frontiers in Ecology and Evolution, 2025)
The structural complexity of host plants plays a significant role in shaping the heterogeneity of phytotelmata, influencing the taxonomic composition and ecological dynamics of associated communities, including medically important organisms such as vector mosquitoes. These microhabitats perform essential ecological functions, such as facilitating nutrient cycling and regulating insect populations, thereby contributing to the stability and conservation of biodiversity in forest environments. In this context, the present study investigated the population fluctuation and species composition of culicids using seven Lecythis pisonis (sapucaia) fruits as natural traps in an Atlantic Forest fragment located in the municipality of Silva Jardim, state of Rio de Janeiro, Brazil, between January 2023 and December 2024. A total of 1,235 specimens were collected. Statistical analyses included the Kruskal-Wallis test followed by Dunn’s post-hoc test. Significant differences in species abundance and richness were observed among the different fruit-traps, which were associated with microenvironmental factors such as light exposure, location, and water accumulation. Aedes albopictus (Skuse, 1895) exhibited clear dominance in a specific microhabitat, while Haemagogus leucocelaenus (Dyar & Shannon, 1924) showed higher prevalence in certain traps, reflecting an aggregated distribution in sites with distinct environmental characteristics and highlighting the importance of entomological surveillance in arbovirus risk areas. Trap 3 showed the highest richness and abundance, making it the most attractive microhabitat, whereas trap 5 demonstrated greater ecological balance among species. Notably, Ae. albopictus and Hg. leucocelaenus, both known vectors of human pathogens, were found among the species collected. The sampling method using sapucaia fruits proved effective, providing a practical and sustainable alternative for monitoring culicid populations in natural environments. The results contribute to our understanding of vector ecology and may inform surveillance and control strategies for mosquito-borne pathogens, as well as support integrated public health and biodiversity conservation actions.